SUPPLY CHAIN MANAGEMENT ANALYSIS OF COMPANY PERFORMANCE THROUGH COMPETITIVE ADVANTAGE STRATEGY - Gaffar, Elvyani NH (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2021)
This study examines supply chain management analysis of companyperformance through a competitive advantage strategy. This study aimsto determine the effect of supply chain management on companyperformance by using (through) a competitive advantage strategy in thebead handicraft industry in the city of Samarinda. The researchmethodology is a quantitative method using PLS data analysistechniques. The population of the bead handicraft industry in the city ofSamarinda is 39 units. The obtained data samples using the censusmethod as a whole from the total population. The result showed thatsupply chain management has a significant positive effect oncompetitive advantage strategy. Compatitive advantage strategy hassignificant positive effect on company performance. The increase incompany performance is influenced by supply chain management byusing (through) a competitive advantage strategy. The benefit of thisresearch is to demonstrate the importance of a competitive advantagestrategy for the bead handicraft industry in the city of Samarindaconcerning improved performance, which in turn will increase sales andprofits.